Teacher Policy Analysis: Challenging the P3K Policy and the Teacher Leader Program Becoming School Principals - Kemal, Selva Noufalia; Duryat, Masduki; Suherman, Aris (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The issues of teacher shortages and employment status disparities have become central concerns in Indonesia’s education system. The government responded with two major policies: the appointment of non-permanent teachers through the Government Employees with Work Agreements (PPPK) scheme and the Transformational Teacher program, which offers a direct pathway to school leadership positions. This article critically analyzes the implementation of both policies in terms of fairness, professionalism, and their impact on the educational ecosystem. The findings reveal that while the PPPK policy provides legal status and improved welfare for non-permanent teachers, it also causes a shortage of teachers in private schools due to large-scale transfers to public schools. Meanwhile, appointing Transformational Teachers as school principals introduces new leadership opportunities but also sparks social tension due to career acceleration that bypasses traditional hierarchical processes. This study recommends a comprehensive evaluation of both policies to ensure they are fair, accountable, and aligned with the actual needs in the field.